Complementary feeding patterns in the first year of life in the city of Rio de Janeiro, Brazil: time trends from 1998 to 2008 - Daniel Alves de Oliveira; Inês Rugani Ribeiro de Castro; Patricia Constante Jaime (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
This study aimed to analyze time trends in complementary feeding practices among children under one year of age in the city of Rio de Janeiro, Brazil, from 1998 to 2008. Based on comparable questions on food consumption in five surveys conducted in representative randomized samples of children in 1998 (n = 3,762), 2000 (n = 3,670), 2003 (n = 4,305), 2006 (n = 3,686), and 2008 (n = 2,621), 16 complementary feeding indicators were constructed. The percentage frequency of all indicators was estimated for each year of the study. Linear trend analyses were also conducted by means of multivariate regression models. All indicators of early complementary feeding decreased from 1998 to 2008. In the 6-11.9 month age group, there was a significant downward trend in the proportion of children receiving food with adequate consistency for their age, consumption of iron-rich foods, and overall adequacy of the diet. A significant upward trend in fruit consumption was observed. There was a decrease in the early complementary feeding, and generally a worsening of complementary feeding practices in children aged 6-11.9 months in Rio de Janeiro during the period studied.